Perbandingan Performa VPN Menggunakan PPTP Dan SSTP Over SSL Dengan Metode Quality of Service - Moezes Rasuanda; Haeruddin haeruddin (Journal of Information System and Technology (JOINT), 2020)
Technology advancement requires high level of security. There are multiple ways for user to improve network security because network security is highly crucial for users with data streaming within the network. Some users of network security are banks, large enterprises, government agencies and other users requiring high network security due to enormous amount of transaction and work-related processes being executed online. Therefore, this becomes important support of network security. Among the ways to secure network is by using VPN which is an easy and commonly used way by users to secure their network. VPN has many types or protocol namely PPTP, L2TP, IPSec, IKEv2, MPLS, SSTP and SSL-VPN. This research is aimed to evaluate and compare performance of two predetermined VPN protocols which are PPTP and SSL protocol using a method called Quality of Service. The method acts as a measure of how well a certain network is, as well as to ensure users achieve best quality and available performance. Keyword: VPN, Virtual Private Network, PPTP, SSL-VPN, Networking